Study on the Hibernation of Tilapia Fish (Oreochromis niloticus)by Usingthe Extract of Ruku-rukuLeaves(Ocimum sanctum L.)during Dry System Transportation - Efendi, Aliusman Mardi; ', Edison; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
(Ocimum sanctum L)extract solution used for hibernating tilapia during drysystem transportation. The research was using an experimental method anddesignedrandomized complete design (RCD). The treatment was hibernating thefish by using four kinds and levelsof the concentrationruku-ruku leaves extract,namely: using cold temperatures 10oC (L0), the solution of ruku-ruku leavesextract at the concentration of 10% (L1), 15% (L2), 20% (L3). Parametersobservedwere the quality of the water used during hibernation (temperature, pH, turbidity,CO2 content), the activity of tilapia during hibernation, the changing conditionsoftilapia during transportation, the temperature fluctuations in the packaging box, aswell as the percentage of survival rate of tilapia after awakening. The resultsshowed that the best treatment was the using of ruku-ruku leaves extract at theconcentration of 20% to hibernate the tilapia fish in 15-20 minutes. The mortalityrate of life of tilapia was up to75% during 6 hours transportation.Key words: dry system transportation, foam media,hibernation,leaves extract,Oreochromis niloticus, Ocimum sanctum.